A p-tert-Butyldihomooxacalix[4]arene Based Soft Gel for Sustained Drug Release in Water - Guo, Hao; Zhang, Runmiao; Han, Ying; Wang, Jin; Yan, Chaoguo (Frontiers in Chemistry, 2020)
Calixarenes and their derivatives are the third generation of macrocyclic hosts in supramolecular chemistry. They are an extremely versatile class of macromolecules due to their superior geometric shapes, excellent flexibility, improved conformational mobility, easily modification and no immune response in vivo. Additionally, they could be functionalized by some groups with good water solubility or biological activity on the upper or lower rim to obtain the derivatives that can be used as the carrier for drugs. P-tert-butyldihomooxacalix[4]arene is a well-known calix[4]arene analog in which one CH2 bridge is replaced by one -O- group. Thus, dihomooxacalix[4]arene has slightly larger cavity than that of calix[4]arene and usually possesses a more flexible cone conformation and the bridged oxygen atom might provide additional binding sites. On the other hand, gels are interesting soft materials owing to their functional properties leading to potential applications. Using gels as drug carriers have attracted tremendous attention for their mumerous advantages to medical treatments, including prolonged drug release time, reduced side effects of drugs and maintain effective plasma concentration. Unfortunately, molecular gels based on p-tert-butyldihomooxacalix[4]arene are rarely reported. Here, we synthesized new functional p-tert-butyldihomooxacalix[4]arene 1 through Ugi reaction in good yield (70%), starting from condensed p-tert-butyldihomooxacalix[4]arene O-alkoxy-substituted benzaldehydes, benzoic acid, benzylamine, and cyclohexyl isocyanide. The soft gel was prepared by adding the 1 into cyclohexane directly. It shows remarkable thermoreversibility and can be demonstrated for several cycles. As is revealed by SEM images, xerogel showed highly interconnected and homogeneous porous network structures, and hence the gel is suitable for storage and controlled release.